Leisure-time aerobic physical activity, muscle-strengthening activity and mortality risks among US adults: the NHANES linked mortality study. Issue 3 (4th October 2013) - Zhao, Guixiang; Li, Chaoyang; Ford, Earl S; Fulton, Janet E; Carlson, Susan A; Okoro, Catherine A; Wen, Xiao Jun; Balluz, Lina S
Abstract : Background: Regular physical activity elicits multiple health benefits in the prevention and management of chronic diseases. We examined the mortality risks associated with levels of leisure-time aerobic physical activity and muscle-strengthening activity based on the 2008 Physical Activity Guidelines for Americans among US adults. Methods: We analysed data from the 1999 to 2004 National Health and Nutrition Examination Survey with linked mortality data obtained through 2006. Cox proportional HRs with 95% CIs were estimated to assess risks for all-causes and cardiovascular disease (CVD) mortality associated with aerobic physical activity and muscle-strengthening activity. Results: Of 10 535 participants, 665 died (233 deaths from CVD) during an average of 4.8-year follow-up. Compared with participants who were physically inactive, the adjusted HR for all-cause mortality was 0.64 (95% CI 0.52 to 0.79) among those who were physically active (engaging in ≥150 min/week of the equivalent moderate-intensity physical activity) and 0.72 (95% CI 0.54 to 0.97) among those who were insufficiently active (engaging in >0 to <150 min/week of the equivalent moderate-intensity physical activity). The adjusted HR for CVD mortality was 0.57 (95% CI 0.34 to 0.97) among participants who were insufficiently active and 0.69 (95% CI 0.43 to 1.12) among those who were physically active. Among adults who were insufficiently active, the adjusted HR for all-cause mortality was 44% lower by engaging in muscle-strengthening activity ≥2 times/week. Conclusions: Engaging in aerobic physical activity ranging from insufficient activity to meeting the 2008 Guidelines reduces the risk of premature mortality among US adults. Engaging in muscle-strengthening activity ≥2 times/week may provide additional benefits among insufficiently active adults.